Evaluation of the genetics of domestic cats (Felis catus) through genes associated with coat in Sahagún, Córdoba, Colombia - Causil-Vargas, Luis Alfonso (2017)
The objective of this study was to evaluate the genetic structure in populations of cat domestic (Felis catus) using markers that encode color, design and length of coat in Sahagún, Córdoba, Colombia. By direct observations during the journey at urban zones belonging to six Sahagún neighborhoods, a total amount of 153 adult cats were randomly studied between months of May and August 2015, using the nomenclature recommended by the Committee on Standardized Genetic Nomenclature for Cats (1968), according to phenotypic markers: O: Orange; a: Non-agouti; Tb: Blotched tabby; d: Dilution; l: Long hair; s: Spotting White; W: Dominant White. Were measured: allele frequencies, gene flow and Hardy-Weinberg equilibrium were calculated through POPGENE 1.31 program; genetic structure using FSTAT v. 2.9.3.2 program. The Spotting White gene showed the highest frequency, the dominant white marker, presented the lowest values of allele frequencies, low genetic differentiation among populations was obtained and high gene flow; an excess of homozygotes was observed to subpopulations and population level. In any population no Hardy-Weinberg equilibrium was found in relation to the Orange and Spotting white markers, and also evidenced natural selection and artificial selection for these markers.